Meaningfulness, feasibility, and usability of quality-of-care measures for maternal and infant health: A structured mixed-methods review - Ryan P. Theis; Rahma S. Mkuu; Hannah Marmol; Lauren Silva; Callie Reeder; Jessica Bahorski; Erica Smith; John C. Smulian; Tony S. Wen; Amanda Redinger; Tabresha Blake; Elizabeth A. Shenkman; et al. (Journal of Clinical and Translational Science)
Abstract